Logarithmic corrections to higher twist scaling at strong coupling from AdS/CFT. - FROLOV, SERGEY (Elsevier, 2007)
We compute 1-loop correction E1 to the energy of folded string in AdS5?S5 (carrying spin S in AdS5 and momentum J in S5) using a ?long string? approximation in which Smuch greater-thanJmuch greater-than1. According to the AdS/CFT the function E1 should represent first subleading correction to strong coupling expansion of anomalous dimension of higher twist SL(2) sector operators of the form TrDSZJ. We show that E1 smoothly interpolates between the lnS regime (previously found in the J?0 case) and the ?/J2ln3(S/J) regime (which is the leading correction to the thermodynamic limit on the spin chain side). This supports the universality of the lnS scaling. As in the previous work, we also find ?non-analytic? corrections related to non-trivial 1-loop phase in the corresponding Bethe ansatz S-matrix.
PUBLISHED
Keywords: Mathematics; Bethe ansatz S-matrix